Pregledni sloj zemljiškokatastrskih načrtov - Radovan, Dalibor (Geodetski vestnik, 1997)
The physical and legal status of all existing cadastral maps in Slovenia was established. On the basis of reviews at the branch offices of regional geodetic administrations two graphical/attribute area type levels were created. The first is composed of areas of equal scale and type of geodetic survey, while the second contains mapped areas of legally invalid status. The following metadata were gathered from maps and their corresponding areas: map name and nomenclature, scale, storage medium, coordinate system, type of survey, legal status, year of production and physical condition
Keywords: kvaliteta; načrti; zemljiški kataster